Designing Interface and User Experience of Elementary School Learning Applications Using Design Thinking - Alifia Nur Aini; Mahendra Wardhana (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Indonesia's entry into the Education 4.0 era emphasizes integrating cyber technology into learning, as reflected in the implementation of the Merdeka Curriculum, which aims to foster the Pancasila Student Profile. Despite this, low student motivation and interest, particularly in mathematics, remain key challenges. This study aims to design an interactive learning application tailored to elementary school students to address these issues. Using the Design Thinking methodology, five stages—empathize, define, ideate, prototype, and test—were employed, involving questionnaires, interviews, usability testing via Maze.co, and user experience evaluation (UEQ). The findings reveal that the application includes structured curriculum-based materials, customizable quizzes, and discussion forums. Usability testing achieved a success rate exceeding 80%, and UEQ results ranged from above average to excellent. Although the application effectively increases engagement and learning outcomes, improvements in visual elements, such as color selection and illustrations, are recommended to enhance the user experience further. This research underscores the significance of user-centered design in creating impactful educational tools that motivate and engage students while supporting educators' instructional goals.